NOTED: Why so much grimness and so little hope? - Allison Oosterman (Asia Pacific Network, 2014)
Book review of: The News: A User’s Manual, by Alain de Botton, London: Hamish Hamilton, 2014, 267pp., ISBN9780241146477.